Mapping the Digital Transformation of Islamic Education: A five-Year Bibliometric Analysis of Online Pedagogical Shifts in Urban and Rural Madrasahs (2020-2024) - Seprianti, Derma; Misbah , Siti; Nurfadilla, Annisa; Novriadi, Dedy; Pakpahan, Fransiskus Novrianto (CV. Lenggogeni Data Publishing, 2024)
The pervasive influence of digital technology in the 21st century has fundamentally reshaped the global educational landscape, compelling Islamic educational institutions to navigate a critical juncture between tradition and modernity. This study employs a comprehensive five-year (2020-2024) bibliometric analysis to map the intellectual structure and research trends of the digital transformation in Islamic education, with a specific focus on online pedagogical shifts in urban and rural madrasahs across Indonesia, the United Arab Emirates, Pakistan, and Palestine. Data from 247 Scopus-indexed documents were analyzed using co-citation and bibliographic coupling techniques in VOSviewer. The findings reveal seven major thematic clusters, highlighting a significant urban-rural dichotomy in digital readiness, the convergence of pedagogical frameworks and technology, and the critical roles of leadership, self-efficacy, and educational resilience. The analysis further identifies a predominant focus on technological efficacy while underscoring gaps in context-specific pedagogical models for Islamic values and strategies to bridge the digital divide. This study concludes by proposing a strategic future research agenda focused on equitable access, value-based digital pedagogy, teacher professional development, and sustainable leadership models. The findings offer valuable insights for policymakers, educators, and researchers in strategizing an inclusive and effective digital future for Islamic education globally.